IMPLEMENTASI MEDIA KARTU KUARTET UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI SISTEM EKSKRESI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Chintya Dea Fadilah; Mohammad Budiyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The world of education today demands innovation in the use of learning media to create a more interactive and meaningful classroom atmosphere. In line with these efforts, this study aims to determine the increase in student learning motivation and learning outcomes through the implementation of quartet cards using the STAD cooperative learning model in the excretory system material. This study used a pre-experimental design with a one group pretest-posttest design. The research subjects were 31 students in class VIII A at a junior high school. Data collection techniques used learning motivation questionnaires and learning outcome tests. Learning motivation data analysis was conducted descriptively, while learning outcomes were analyzed using normality tests to determine data distribution. Furthermore, N-Gain calculations and paired sample t-tests were conducted to determine the increase and significance of student learning outcomes. The results showed an increase in student learning motivation, as indicated by an average motivation questionnaire score of 47.72 to 82.53. Student learning outcomes also improved, with an average N-Gain value of 0.51, which is classified as moderate. The results of the paired sample t-test on learning outcomes showed a significance value of < 0.05, so it can be concluded that the implementation of quartet cards using the STAD cooperative learning model can increase student motivation and learning outcomes in the subject of the excretory system.